The role of inhibitory dynamics in the loss and reemergence of macropodoid tooth traits. (18th February 2016) - Couzens, Aidan M. C.; Evans, Alistair R.; Skinner, Matthew M.; Prideaux, Gavin J.
Abstract : The reversibility of phenotypic evolution is likely to be strongly influenced by the ability of underlying developmental systems to generate ancestral traits. However, few studies have quantitatively linked these developmental dynamics to traits that reevolve. In this study, we assess how changes in the inhibitory cascade, a developmental system that regulates relative tooth size in mammals, influenced the loss and reversals of the posthypocristid, a molar tooth crest, in the kangaroo superfamily Macropodoidea. We find that posthypocristid loss is linked with reduced levels of posterior molar inhibition, potentially driven by selection for lophodont, higher‐crowned molar teeth. There is strong support for two posthypocristid reversals, each occurring after more than 15 million years of absence, in large‐bodied species of Macropus, and two giant extinct species of short‐faced sthenurine kangaroo ( Procoptodon ). We find that whereas primitive posthypocristid expression is linked to higher levels of posterior molar inhibition, reemergence is tied to a relative increase in third molar size associated with increasing body mass, producing molar phenotypes similar to those in mouse where the ectodysplasin pathway is upregulated. We argue that although shifts in the inhibitory cascade may enable reemergence, dietary ecology may limit the frequency of phylogenetic reversal.